Determinants of SME Tax Reporting Compliance: Roles of Digitalization Tax and Tax Knowledge - Muhammad Irfan Dary Rahmatullah; Siti Sundari; Vicky Vendy (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This research is fundamentally motivated by the ongoing phenomenon of the relatively low tax ratio in Indonesia. This condition indicates that state tax revenue is not yet optimal, especially from the small and medium enterprise (SME) sector which largely dominates the national economy. The government continuously strives to enhance tax compliance, notably through the modernization of digital-based tax administration systems. Consequently, this study aims to analyze and empirically prove the effect of tax digitalization and tax knowledge levels on tax reporting compliance among SME actors in the East Java region. A quantitative approach was systematically employed for this investigation. Primary data was collected via questionnaires directly distributed to 99 SME respondents operating in East Java. The sampling technique utilized was the accidental sampling method, with the precise sample size determined by the Lemeshow formula. Furthermore, data analysis was meticulously conducted using Partial Least Square - Structural Equation Modeling (PLS-SEM) through SmartPLS software. The empirical findings reveal an R-Square value of 0.627, meaning the independent variables successfully explain 62.7% of the dependent variable's variance. Crucially, the study proves that tax digitalization has a positive and highly significant impact on tax reporting compliance. Furthermore, the level of tax knowledge also significantly and positively influences tax reporting compliance. The practical implication of this research strongly suggests that accessible digital tax systems and adequate taxpayer understanding are absolutely crucial factors in encouraging SME actors to consistently fulfill their tax reporting obligations.